2016
DOI: 10.1177/0192513x16662102
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Support Exchange Between Grandparents and Grandchildren in Rural China: The Roles of Grandparent Caregiving, Patrilineal Heritage, and Emotional Bonds

Abstract: Mutuality of support provision is a necessary precondition of family solidarity. However, the exchange of care between grandparents and grandchildren has largely been neglected. Using data from the fourth wave of the Anhui Study in China, this study investigated determinants of support exchange between grandparents and grandchildren. Results showed that more grandparents received support from than provided support to their grandchildren. A higher percentage of older adults exchanged support with the grandchild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 51 publications
6
25
1
1
Order By: Relevance
“…In this study, the middle generation, especially their filial obligation behavior toward old parents also played an important role in the grandparent–grandchild relationship. This result confirms previous study findings that the middle generation facilitated the close relationship between grandparent and grandchild ( Xu & Chi, 2018 ; Xu et al, 2014 ). Filial obligation is a traditional Chinese value and can be defined as the expression of responsibility, respect, sacrifice, and family harmony that regulates children’s attitudes and behavior.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the middle generation, especially their filial obligation behavior toward old parents also played an important role in the grandparent–grandchild relationship. This result confirms previous study findings that the middle generation facilitated the close relationship between grandparent and grandchild ( Xu & Chi, 2018 ; Xu et al, 2014 ). Filial obligation is a traditional Chinese value and can be defined as the expression of responsibility, respect, sacrifice, and family harmony that regulates children’s attitudes and behavior.…”
Section: Discussionsupporting
confidence: 93%
“…The middle generation often influences intergenerational relationships by encouraging or hindering interaction between grandparents and grandchildren in Asian population ( Xu & Chi, 2015 ). Positive relationships between grandparents and grandchildren in China were possible only if they were mediated and facilitated by the parents ( Xu & Chi, 2018 ; Xu, Silverstein, & Chi, 2014 ). For immigrant families, one study found that the link between Australian Vietnamese grandparents and their grandchildren was dependent upon the link between the grandparent and parent generations ( Vo-Thanh-Xuan & Liamputtong, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese Academy of Social Science's 2008 survey of five urban cities in China (Guangzhou, Hangzhou, Zhengzhou, Lanzhou, and Harbin) found a bilateral pattern of grandparents' child-care support, with 48.3% of the surveyed families using paternal grandparent child care and 53.2% using maternal grandparent child care (Ma, Shi, Li, Wang, & Tang, 2011). A similar trend was observed even in rural China (Xu & Chi, 2018;W. Zhang, 2009), where traditional patrilineal culture has been particularly persistent.…”
Section: Methodsupporting
confidence: 72%
“…Results of the present study showed a significant association between the level of education and grandparent-grandchild relationship and supported previous studies documented higher level of education of older adults improve grandparent-grandchild relationship [27, 28].…”
Section: Discussionsupporting
confidence: 92%